Small DNA pieces in C. elegans are intermediates of DNA fragmentation during apoptosis. - P Joseph Aruscavage; Sabine Hellwig; Brenda L Bass (PLoS ONE)
While studying small noncoding RNA in C. elegans, we discovered that protocols used for isolation of RNA are contaminated with small DNA pieces. After electrophoresis on a denaturing gel, the DNA fragments appear as a ladder of bands, approximately 10 nucleotides apart, mimicking the pattern of nuclease digestion of DNA wrapped around a nucleosome. Here we show that the small DNA pieces are products of the DNA fragmentation that occurs during apoptosis, and correspondingly, are absent in mutant strains incapable of apoptosis. In contrast, the small DNA pieces are present in strains defective for the engulfment process of apoptosis, suggesting they are produced in the dying cell prior to engulfment. While the small DNA pieces are also present in a number of strains with mutations in predicted nucleases, they are undetectable in strains containing mutations in nuc-1, which encodes a DNase II endonuclease. We find that the small DNA pieces can be labeled with terminal deoxynucleotidyltransferase only after phosphatase treatment, as expected if they are products of DNase II cleavage, which generates a 3' phosphate. Our studies reveal a previously unknown intermediate in the process of apoptotic DNA fragmentation and thus bring us closer to defining this important pathway.